Alternative design of foundations subjected to uplift for transmission line tower - Narayanan Nair, Purushothaman Nair (2006)
Transmission line is a medium to carry power loads from one station to another station, therefore; it is one of the most important projects in power business. An efficient design of foundations for transmission line towers has always been a challenge for the engineers due to the variety and cyclic nature of the loads. Foundations especially for the four legged type are subjected to combinations of all types of loads i.e: compression, uplift, torsion and shear. The current practice of non-shored excavation for the construction of the transmission tower foundation does not comply with the safety regulation. Thus, the main objective of this study is to evaluate current design practices for standard undercut foundations (1 Undercut and 2 Undercut) for transmission line projects undertaken by TNB. Furthermore, alternative foundation design and their performance will be in term of safety and concrete volume. The study is based on an ongoing project i.e a 275Kv Transmission Line from Melaka to Kelemak. In this research, drilled shaft was identified as alternative foundation for transmission line towers. Even-though the construction cost is higher than the conventional method, but drilled shaft can eliminate or reduce unsafe act and unsafe condition thus will reduce the incidents or near misses. Furthermore drilled shaft also comply with the requirement of FMA and OSHA which was identified as a main objective of this study.